The myth of medical multiculturalism: how social closure marginalises traditional Chinese medicine in New Zealand. Issue 3 (2nd September 2022) - Palatchie, Brittany; Beban, Alice; Andersen, Barbara
ABSTRACT: This article uses neo-Weberian social closure theory and Bourdieu's theory of symbolic violence to examine the epistemic tension between biomedicine and traditional Chinese medicine (TCM) in Aotearoa New Zealand (NZ), a country that aspires to a multicultural model of healthcare. Drawing on interviews with TCM practitioners and analysis of TCM practitioners' attempt to become a regulated profession, we argue that a multicultural health model remains a myth as biomedical stakeholders deploy material and symbolic forms of social closure that limit the scope of TCM practice. Discourses of the need for scientific evidence, public safety, qualification standards and English language fluency undermine the culturally distinctive but pragmatic forms of medicine that TCM practitioners utilise. This has implications for TCM as practitioners are denied public funding, their scope of practice is limited, and the expectations for TCM to conform to a biomedical model of healthcare have created tensions within the TCM community.